Observation of the Crossover from Photon Ordering to Delocalization in Tunably Coupled Resonators - Collodo, Michele C.; Potocnik, Anton; Gasparinetti, Simone; Besse, Jean-Claude; Pechal, Marek; Sameti, Mahdi; Hartmann, Michael J.; Wallraff, Andreas; Eichler, Christopher (Physical Review Letters, 2019)
Networks of nonlinear resonators offer intriguing perspectives as quantum simulators for nonequilibrium many-body phases of driven-dissipative systems. Here, we employ photon correlation measurements to study the radiation fields emitted from a system of two superconducting resonators in a driven-dissipative regime, coupled nonlinearly by a superconducting quantum interference device, with cross-Kerr interactions dominating over on-site Kerr interactions. We apply a parametrically modulated magnetic flux to control the linear photon hopping rate between the two resonators and its ratio with the cross-Kerr rate. When increasing the hopping rate, we observe a crossover from an ordered to a delocalized state of photons. The presented coupling scheme is intrinsically robust to frequency disorder and may therefore prove useful for realizing larger-scale resonator arrays.
CRIS-Team Scopus Importer:2022-06-27